The effectiveness of the control procedures for administration Face Corona Pandemic (covid-19) in Iraq - Salem, Dhia; Qaddouri, Tagreed (Journal of Legal Sciences, 2023)
The spread of the Corona virus (COVID-19) has led to the use of public authorities to take a range of preventive measures and preventive measures to reduce and combat its prevalence. Adapt to the new position and reduce the spread of the epidemic, and the most important measures taken by the Sonato authorities are closing of some commercial activities, disrupting transport, domestic and social quarantine , and asylum to the partial option for public utilities.